Ethnopolitical processes as determinants of ethnopolitical management in Eastern European countries in the context of sub-regional security - Karolak-Michalska, Magdalena (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The following article discusses ethnopolitical processes (politicization of ethnicity and ethnopolitical mobilization of national and ethnic minorities) in Eastern European countries. The author analyses social and political activity of national and ethnic minorities, as well as their representation in state authorities of the Republic of Belarus, Republic of Moldova and Ukraine, and concludes that those processes affect the national security of the countries that make up the sub-region. Particular threat to national security is posed by organized separatist actions. In case of the Republic of Belarus, the problem is not observed, but in the Republic of Moldova (Gagauzia, Transnistria) and Ukraine (Donbas, Carpathian Ruthenia) it is a very serious issue. Separatist tendencies of various ethnic groups have a significant impact on the national security policy. They also call for intervention by state authorities, not only in connection with security issues, but also in relation to appropriate management of ethnopolitical processes within the country.

Artykuł przedstawia problematykę procesów etnopolitycznych (polityzacji etniczności, mobilizacji etnopolitycznej mniejszości narodowych i etnicznych) w państwach Europy Wschodniej. Autorka analizując aktywność społeczno-polityczną oraz udział mniejszości narodowych i etnicznych w organach władzy Republiki Białorusi, Republiki Mołdawii, Ukrainy dochodzi do wniosku, że procesy te wpływają na bezpieczeństwo państw subregionu. Szczególne znaczenie dla bezpieczeństwa państw mają te zorganizowane aktywności, które zgłaszają działania separatystyczne. W przypadku Republiki Białorusi problem ten nie występuje, natomiast w Republice Mołdawii (Gagauzja i Naddniestrze) i na Ukrainie (Donbas, Zakarpacie) ma realny wymiar. Tendencje separatystyczne poszczególnych grup etnicznych stanowią istotny element w kształtowaniu polityki bezpieczeństwa państwa. Stają się również przestrzenią, w której konieczna jest reakcja władz państwowych, w tym dotycząca nie tylko bezpieczeństwa, ale także umiejętnego zarządzania procesami etnopolitycznymi w państwie.
Procesy etnopolityczne jako jedno z uwarunkowań zarządzania etnopolityką w państwach Europy Wschodniej a bezpieczeństwo subregionu
Keywords: ethnopolitical processes; ethnic and national minorities; Eastern Europe; security threat; post-Soviet area; procesy etnopolityczne; mniejszości narodowe i etniczne; Europa Wschodnia; bezpieczeństwo; przestrzeń poradziecka